Genetic diversity and prevalence of extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella pneumoniae in aquatic environments receiving untreated hospital effluents. (16th December 2022) - Girijan, Sneha Kalasseril; Pillai, Devika
Abstract: The spread of extended-spectrum beta-lactamase (ESBL)-producing bacteria in the environment has been recognized as a challenge to public health. The aim of the present study was to assess the occurrence of ESBL-producing Escherichia coli and Klebsiella pneumoniae from selected water bodies receiving hospital effluents in Kerala, India. Nearly 69.8% of Enterobacteriaceae isolates were multi-drug resistant by the Kirby–Bauer disc diffusion method. The double disc synergy test was used to detect the ESBL production and the genes responsible for imparting resistance were detected by PCR. Conjugation experiments confirmed the mechanism of plasmid-mediated transfer of resistance. The prevalence of ESBL production in E. coli and K. pneumoniae was 49.2 and 46.8%, respectively. Among the ESBL-encoding genes, bla CTX-M was the most prevalent group followed by bla TEM, bla OXA, bla CMY, and bla SHV . The results suggest that healthcare settings are one of the key contributors to the spread of ESBL-producing bacteria, not only through cross-transmission and ingestion of antibiotics but also through the discharge of waste without a proper treatment, leading to harmful effects on the aquatic environment. The high prevalence of ESBL-producing Enterobacteriaceae with resistance genes in public water bodies even post-treatment poses a serious threat. HIGHLIGHTS: ESBL-producing E. coli and K. pneumoniae were detected in hospital effluent samples. The prevalence of ESBL production in E. coli and K. pneumoniae was 49.2 and 46.8%. bla CTX-M was the most prevalent among the ESBL-encoding genes. The conjugation experiment proved the horizontal mode of gene transfer. Hospitals play a significant role in the spread of antibiotics and resistant bacteria. Graphical Abstract